(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
“Feminism” ordinarily means “the belief that men andwomen should have equal rights and opportunities”. It is also an organisedactivity in support of women’s rights and interests. It is a collection ofmovements and ideologies aimed at defining, establishing and defending equalpolitical, economic and social rights for women. A feminist pleads or supportsthe rights and equality of women. Feminism in India aims at defining, establishing anddefending equal political and social rights as well as equal opportunities forIndian women. Feminism in Indian Fiction in English is, as commonly conceived,is a very sublime and over-the-top concept handled subtly under restrictedcircumstances. India women writers have often raised variety of themes in astyle that usually poetry and novels are capable of offering. Indian writershave often raised their voice against social and cultural inequality thatconstrained women’s liberty and perpetrated institutional seclusion of women.Kamla Das explores the women’s plight suffering in their days to day life.Shashi Desponde deals with remorseful condition of women. Bapsi Sidhwahighlights socio-economic condition of Parsi women. R.K. Narayan is concernedabout house-wives of middle class families. Mulk Raj Anand satirizes thesocio-religious hypocrisy prevalent in various walks of society. Anita Desaiprimarily deals with human conditions of suffering women. Kamla Markandeya optsthe theme of east-west encounters. Salman Rushdie is worried about sexual abuseof children. Shobha De presents a concept of new women who totally ridicule thetraditional way of life. So, Indian writers in English are keenly aware ofwomen related issues and they plead for gender equality in their own way. The word feminism refers to the advocacy of women’s rightseeking to remove restrictions that discriminate against women. It relates tothe belief that women should have the same social, economic and politicalrights as men. Feminism has often focused upon what is absent rather than whatis present. The word feminist refers to the person who advocates or practicesfeminism and it takes political position. Female is the matter of biology andfeminine is a set of culturally defined characteristics. Indian feminists havealso fought against cultural issues within the patriarchal society, such asinheritance laws and practice of widow immolation known as sati. Unlike thewestern feminist movements, India’s movement was initiated by men and thenjoined by women.